2022
DOI: 10.1038/s43017-022-00309-5
|View full text |Cite
|
Sign up to set email alerts
|

Stability of the Antarctic Ice Sheet during the pre-industrial Holocene

Abstract: The rate and magnitude of the Antarctic Ice Sheet (AIS) contribution to global sea-level rise beyond 2100 ce remains highly uncertain. Past changes of the AIS, however, offer opportunities to understand contemporary and future ice sheet behaviour. In this Review, we outline how the AIS evolved through the pre-industrial Holocene, 11,700 years ago to 1850 ce. Three main phases of ice sheet behaviour are identified: a period of rapid ice volume loss across all sectors in the Early and Mid Holocene; a retreat inl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
21
0

Year Published

2022
2022
2025
2025

Publication Types

Select...
3
3
2

Relationship

0
8

Authors

Journals

citations
Cited by 30 publications
(23 citation statements)
references
References 241 publications
2
21
0
Order By: Relevance
“…However, because the WAIS is also sensitive to ice-dynamical changes at the ice-sheet margins (e.g. GL retreat and/or calving), an increase in accumulation rates in the upper part of the ice sheet may not necessarily result in enough thickening to counteract potential losses from ice dynamics further downstream (Jones et al, 2022). The lack of an ice-dynamical component in the model used here precludes us from reaching such a conclusion; however, higher accumulation rates of up to 18% during the mid-Holocene across 30% of the WAIS would likely be consistent with an increase of several tens of meters in ice thickness (e.g.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…However, because the WAIS is also sensitive to ice-dynamical changes at the ice-sheet margins (e.g. GL retreat and/or calving), an increase in accumulation rates in the upper part of the ice sheet may not necessarily result in enough thickening to counteract potential losses from ice dynamics further downstream (Jones et al, 2022). The lack of an ice-dynamical component in the model used here precludes us from reaching such a conclusion; however, higher accumulation rates of up to 18% during the mid-Holocene across 30% of the WAIS would likely be consistent with an increase of several tens of meters in ice thickness (e.g.…”
Section: Discussionmentioning
confidence: 99%
“…sectors initially retreated from the LGM inland until ~9.7 -10.2 ka, and then re-advanced to its modern position sometime during the Holocene. Although they attributed this change in GL position to the solid Earth viscoelastic response due to ice-sheet mass change and the subsequent re-grounding around pinning points, it has also been suggested that an increase in accumulation rates upstream of the GL could lead to a re-advance via ice thickening there and a subsequent increase in ice flow (Steig et al, 2001;Koutnik et al, 2016;Jones et al, 2022).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Recent studies 12,[29][30][31] suggest that during the Holocene, the meltwater contribution of the AIS was comparatively modest. A small Antarctic contribution from 9 to 7 ka is supported by our RSL data (Fig.…”
Section: Data-model Comparison and Meltwater Partitioningmentioning
confidence: 99%
“…As a result, uncertainty of our projections is dominated by the unknown strength of marine ice‐sheet feedbacks and internal climate variability (Robel et al., 2019). Records of ice‐sheet change in the geologic past (i.e., paleoglaciological reconstructions) provide a pathway for constraining the limits of ice‐mass changes over societally relevant timescales (Jones et al., 2022; Kopp et al., 2016), and as a result, may reduce the uncertainty envelope in projections of future sea level rise (e.g., DeConto et al., 2021).…”
Section: Introductionmentioning
confidence: 99%